2023
DOI: 10.1002/pc.27598
|View full text |Cite
|
Sign up to set email alerts
|

Temperature‐dependent inter‐laminar fracture behavior of waste short carbon fiber embedded glass fiber/epoxy composites

Abstract: Delamination is one of the life‐limiting failure modes for fiber reinforced polymer (FRP) composite composites resulting in poor damage tolerance, as this failure mode occurs at considerably lower loads. Owing to the enormous demand and mass production of FRP composites, a large amount of fiber waste is produced worldwide. This triggers concern about utilizing these fiber wastes for some valuable applications. The present study aims to improve the overall damage tolerance of laminated glass/epoxy composites vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 131 publications
(214 reference statements)
0
1
0
Order By: Relevance
“…[11][12][13] Therefore, improving the interlaminar shear strength (ILSS) of FRPs and healing the damage are key issues for enhancing the service life of composites. [14][15][16][17][18][19][20] Previous studies have shown that developing a nanoparticle-modified matrix with improved toughness can enhance the mechanical properties of FRPs, 21 since the matrix is a key component of composites that can dominate the toughness of FRPs. [22][23][24][25][26][27][28] For example, Park et al 22 used ozone-treated single-walled carbon nanotubes to toughen carbon-fiber (CF)-reinforced epoxy (EP) composites, and the ILSS and fracture toughness of the composites increased by 79.98% and 54.59%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] Therefore, improving the interlaminar shear strength (ILSS) of FRPs and healing the damage are key issues for enhancing the service life of composites. [14][15][16][17][18][19][20] Previous studies have shown that developing a nanoparticle-modified matrix with improved toughness can enhance the mechanical properties of FRPs, 21 since the matrix is a key component of composites that can dominate the toughness of FRPs. [22][23][24][25][26][27][28] For example, Park et al 22 used ozone-treated single-walled carbon nanotubes to toughen carbon-fiber (CF)-reinforced epoxy (EP) composites, and the ILSS and fracture toughness of the composites increased by 79.98% and 54.59%, respectively.…”
Section: Introductionmentioning
confidence: 99%